Discovery of a new species of Inocelliidae (Insecta: Raphidioptera) in an altitude of nearly 3500 m in China - Liu, Xingyue; Lyu, Yanan; Aspöck, Horst; Aspöck, Ulrike (Zootaxa, 2018)
A new snakefly species of the family Inocelliidae is described from China: Inocellia occidentalis sp. nov. The new species belongs to the Inocellia crassicornis species group.